Synthesis, Spectral, Modeling, Docking and Cytotoxicity Studies on 2‐(2‐aminobenzoyl)‐N‐ethylhydrazine‐1‐carbothioamide and its divalent metal complexes. (11th July 2020) - Hosny, Nasser Mohammed; Hussien, Mostafa A.; Motawa, Rana; Belal, Arafa; Abdel‐Rhman, Mohamed H.
Abstract : 2‐(2‐aminobenzoyl)‐N‐ethylhydrazine‐1‐carbothioamide (H3 L) and its Cu (II), Co (II), Ni (II) and Zn (II) complexes have been synthesized. The structures of the isolated compounds were suggested based on elemental analyses, spectral analyses (FTIR, 1 H and 13 CNMR, MS, ESR and UV–Visible) and magnetic moments measurements. The free ligand exists in the keto‐thione form, while in the metal complexes; it exists in the enol form and coordinates as mononegative bidentate via deprotonated enolic oxygen and N 2 H nitrogen. Both Co (II) and Ni (II) complexes have an octahedral, while Cu (II) complex has a square planar geometry. The compounds have direct electronic transitions with optical band gap ( E g ) values in the range 3.14–3.40 eV. The ligand and its complexes were optimized using DFT/B3LYP methodology. The ligand optimization results supported the involvement of the carbonyl oxygen, thione sulfur and N 2 H hydrogen atoms in hydrogen bonding formation. Furthermore, the obtained structures of the ligand and its complexes were subjected to molecular docking study to predict interactions cause their cytotoxicity. Finally, the in vitro cytotoxicity activities of the ligand and its complexes were investigated against Hela and WISH cell lines where the Zn (II) complex exhibited higher activity than the other compounds against the two cell lines in accordance with molecular docking suggestion. Abstract : 2‐(2‐aminobenzoyl)‐N‐ethylhydrazine‐1‐carbothioamide (H3 L) and its Cu (II), Co (II), Ni (II) and Zn (II) complexes have been synthesized.The ligand chelates to the metals as mononegative bidentate via deprotonated enolic oxygen and N 2 H nitrogen.The in vitro cytotoxicity activity investigated against Hela and WISH cell lines where the Zn (II) complex presented more potent than ligand.